Activation-free supercapacitor electrode based on surface-modified Sr2CoMo1-xNixO6-δ perovskite - Liu, Y.; Wang, Z.; Zhong, Yijun; Xu, Xiaomin; Veder, Jean-Pierre; Rowles, Matthew; Saunders, M.; Ran, R.; Shao, Zongping (ELSEVIER SCIENCE SA, 2020)
Oxygen anion intercalation-type supercapacitors are promising charge storage devices. In this study, by taking advantage of the capability of selective exsolution of elements from perovskite lattice, a nanoparticles-modified perovskite composite is developed as new perovskite-based electrode for supercapacitor with further improved performance that allow the energy storage via two different mechanisms, i.e., Faradaic surface redox pseudocapacitance and oxygen anion-intercalation pseudocapacitance. The derived supercapacitor shows high power density and energy density, and no surface activation process, and stable performance. Specifically, perovskite oxides with the nominal composition of Sr2CoMo1-xNixO6-δ are designed and the strategy of controlled in-situ exsolution and re-oxidation of B-sites Ni and Co element to create Co3O4 and NiO nanoparticles on the perovskite surface and extra oxygen vacancies in perovskite bulk is applied. The Co3O4 and NiO nanoparticles on surface of electrode are found to effectively improve the surface redox pseudocapacitance, while the creation of additional oxygen vacancies enhances the oxygen anion intercalation pseudocapacitance. Consequently, the electrode displays excellent charge storage capability with a stable capacity as high as ~930 F g−1 and superior rate performance. As a universal strategy, it may also be applicable for the design and synthesis of alternative high-performance electrodes with mixed energy storage mechanisms.